2021
DOI: 10.1049/cth2.12197
|View full text |Cite
|
Sign up to set email alerts
|

Time‐iteration‐domain integrated learning control for robust trajectory tracking and disturbance rejection: With application to a PMLSM

Abstract: Iterative learning control (ILC) has been widely used to improve motion performance when reference trajectories and external disturbances are strictly repetitive. However, the occurrence of non‐repetitive trajectories and disturbances would significantly deteriorate the performance of traditional ILC methods. To solve this problem, a time‐iteration‐domain integrated learning control (TIDLC) scheme is proposed for enhancing robustness against non‐repetitive trajectories and disturbances. The TIDLC scheme consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For a repetitive trajectory tracking task, ILC derives the optimal compensation term by previous tracking errors so as to improve tracking accuracy. Generally, the compensation term of ILC can be injected into reference trajectory before the closed-loop system [37]- [39] or control input before the plant [40]- [42]. The former arrangement is Serial ILC (Fig.…”
Section: A Iterative Learning Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…For a repetitive trajectory tracking task, ILC derives the optimal compensation term by previous tracking errors so as to improve tracking accuracy. Generally, the compensation term of ILC can be injected into reference trajectory before the closed-loop system [37]- [39] or control input before the plant [40]- [42]. The former arrangement is Serial ILC (Fig.…”
Section: A Iterative Learning Controlmentioning
confidence: 99%
“…Recently, an accuracy-oriented cascaded ILC (CILC) approach has been proposed to further reduce the residual error of standard ILC [41], [42]. To extend the scope of ILC applications, researchers have also contributed to enhancing extrapolation capability for non-repetitive trajectories [39] and robustness to accidental external disturbances [40]. However, ILC is merely suitable for repetitive trajectory tracking tasks and sensitive to trajectory changes.…”
Section: Introductionmentioning
confidence: 99%
“…Because it does not depend on the model of the controlled object and has strong adaptability, the PID controller is the most widely used control strategy in current PMLSM servo systems, such as the current loop controller or speed loop controller based on PID [15,16]. To ensure that the motor has good dynamic operation characteristics under actual operating conditions, the PMLSM servo system will combine new control methods with a PID controller to improve the system performance, such as the fuzzy control strategy [17], sliding mode controller [18], and iterative learning control methods [19]. In the literature [20], an internal model control PID method based on a linear extended state observer model was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The ILC scheme has emerged as a very important tool due to its novel theoretical development and their applications; for example, in recent years, the ILC scheme has been combined with a MPC in order to address tracking trajectory problems (see reference Liang et al [1]), and its performance has been improved using model-free disturbance observers, which are commonly used in systems that require a precise motion, thus enhancing the robustness of the system (see Su [2]). Also, in Liu et al [3], to avoid the deterioration of the classical ILC scheme due to the witticism of non-repeated trajectories and disturbances, a TIDLC scheme is proposed for improving robustness. At the beginning, the experimental evidence showed that the P-Type Law works properly concerning nonlinear robot dynamics.…”
Section: Introductionmentioning
confidence: 99%